Implementasi Kebijakan Pengembangan Kompetensi berbasis E-learning melalui Program Flexible Micro Learning di Instansi Pemerintah - Widaningsih Widaningsih (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2026)
This study analyses the implementation of e-learning-based competency development policy at the Center for Learning and Policy Strategy for National Civil Service Talent, National Institute of Public Administration through the Flexible Micro Learning (FML) program. The research employs a descriptive quantitative approach using Edwards III's policy implementation model, which encompasses communication, resources, disposition, and bureaucratic structure dimensions. Data were collected from 54 civil servants participating in the FML program through questionnaires and structured interviews. The findings indicate that policy implementation falls into the